2012
DOI: 10.1371/journal.pone.0031131
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Objective, Multivariate Biomarkers Composed of Plasma Amino Acid Profiles for the Diagnosis and Assessment of Inflammatory Bowel Disease

Abstract: BackgroundInflammatory bowel disease (IBD) is a chronic intestinal disorder that is associated with a limited number of clinical biomarkers. In order to facilitate the diagnosis of IBD and assess its disease activity, we investigated the potential of novel multivariate indexes using statistical modeling of plasma amino acid concentrations (aminogram).Methodology and Principal FindingsWe measured fasting plasma aminograms in 387 IBD patients (Crohn's disease (CD), n = 165; ulcerative colitis (UC), n = 222) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 26 publications
5
131
0
2
Order By: Relevance
“…Also Hisamatsu et al [52] distinguished between patients (UC and CD) with active disease and those in remission using plasma aminograms. Other studies failed to distinguish between active and inactive IBD [44,50] .…”
Section: Disease Activity-related Metabolitesmentioning
confidence: 99%
“…Also Hisamatsu et al [52] distinguished between patients (UC and CD) with active disease and those in remission using plasma aminograms. Other studies failed to distinguish between active and inactive IBD [44,50] .…”
Section: Disease Activity-related Metabolitesmentioning
confidence: 99%
“…The analytical techniques used to study the metabolome, include gas chromatography (GC), liquid chromatography (LC) and high/ultra-performance liquid chromatography (H/UPLC) followed by mass spectrometry (MS), and nuclear magnetic resonance spectroscopy (NMR) 54 . Different metabolomic approaches have been applied in human biomaterials, including fecal water extracts, blood serum and urine samples, aiming to discriminate IBD patients from control subjects [55][56][57][58][59][60][61][62] . Furthermore, 1 H NMR spectroscopy and LC-MS have revealed distinct metabolic profiles between different intestinal compartments 63 .…”
Section: E Constructing the Ibd Metabolomementioning
confidence: 99%
“…32 Interestingly, amino acid profiling revealed decreased levels of plasma histidine concentration in the patients with active Crohn' s disease. 33 We have demonstrated that several molecules can affect the differentiation of monocytes to DCs. Am80, a synthetic retinoic acid receptor (RAR) agonist, promotes the differentiation of monocytes to an IL-12p70 hypo-producing DC phenotype with a reduced Th1 polarizing ability.…”
Section: Conditioning and Control Of Differentiation Of Innate Immunementioning
confidence: 96%